A Month-by-Month Long-Term Study on Carbamazepine: Clinical, EEG and Pharmacological Evaluation. (March 1979) - Monaco, F; Riccio, A; Fantini, M; Baruzzi, A; Morselli, P L
Carbamazepine plasma levels were monitored for a twelve-month period in twenty epileptic patients. Seizure frequency decreased remarkably on inclusion of the drug in the therapy and attainment of plasma levels of 7–9 μg/ml. A faster breakdown rate in children was confirmed, while carbamazepine-10, 11-epoxide was present for carbamazepine levels above 4–5 μg/ml. EEG tracings did not show substantial modifications; this variable was thus considered to be of little value in assessing the clinical picture. Side-effects were minimal. Carbamazepine is increasingly becoming the drug of first choice in the management of both generalized and partial epilepsy, while better and more rapid results are obtained in monotherapy.